NOTES ON THE PALM FLORA OF CENTRAL SUMATRA - John Dransfield (REINWARDTIA, 1974)
In July and August 1972, I spent five weeks on an expedition to study rattans and other palms in the provinces of Jambi and West Sumatra. This central area of Sumatra was chosen because expeditions have already been made to South Sumatra in February 1971 and March 1972 and to North Sumatra and Aceh with the Kyoto University Expedition in August 1971, and therefore collections made in this central area would link up collections from the south and north and would hence add considerably to our knowledge of the palm flora of this rich island. After advice from the Department of Nature Conservation in Jambi and from Dr. M. Jacobs in Rijksherbarium (Leiden) had been considered, it was decided to work westwards from Berbak Nature Reserve on the east coast near Nipah Panjang, to the Bukit Barisan, the main range of Sumatra, to Gunung Kerinci Nature Reserve and G. Tujuh near Sungai Penuh and from there, across the western part of the Bukit Barisan to Padang and Bukittinggi. From Bukittinggi it was planned to visit the Kafflesia arnoldii Nature Reserve at Batang Palupuh, and then return to Jambi by way of Muara Tebo and Muara Tembesi, where reputedly there still exists lowland forest. By more or less confining our collecting activities to the normally neglected Palmae it was hoped that within the time available a large area could be covered reasonably, and a palm transect for central Sumatra made. Two assistants from Bogor accompanied me to help in the difficult task of collecting rattans: Dedy Darnaedi (Herbarium Bogoriense) and Abdul Hanan (Kebun Raya). These assistants were also given individual collecting assignments as part of a scheme for training assistants in field botany. Dedy was to collect Pteridophyta and Hanan to collect material for growing in the Kebun Raya. Soetrisno Soewoko, head of Nature Conservation in Jambi accompanied us throughout tha expedition.